7 - “The (Re)Making of Bodies and Enforcement of Masculinities: Aesthetics and Aspiration at a Zimbabwean University” - Mangezvo, Pedzisayi Leslie (Africa Development, 2018)
Drawing on a qualitative study of students from Africa University, Zimbabwe, this article explores the materiality of skin bleaching and skin whitening in asserting and enforcing current constructions of aspirational masculinities. The article reflects on how discourses of skin bleaching and skin whitening among University students present a prism through which we can interrogate hierarchies of male identities, the notions of “colourism”, aspiration and aesthetics among young African males in the twenty-first century. The article argues that skin bleaching and whitening among the students has incubated a colour stratification in the university that is redefining what it means to be a man, the dynamics of aesthetics, beauty and masculinities. Based on the analysis of empirical data from open-ended interviews, the article concludes that sensuality, beauty, male identities and the (re)making of bodies among the university students remain contested terrains that evoke numerous emotions and masculine sensibilities.